2014
DOI: 10.3844/jcssp.2014.2240.2252
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pricing With Updated Demand for the Sports and Entertainment Ticket Industry

Abstract: Revenue Management (RM) helped increase profitability for many travel industries. Selling perishable products with a fixed event date, the Sports and Entertainment (S&E) ticket industry can potentially benefit from RM ideas but has received less attention in the literature. In this study we develop dynamic pricing models for stochastic S&E demand in a discrete finite time setting, where demand depends not only on ticket prices but also on remaining times until the show dates. We assume the show popularity is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Cui et al (2012) [46] examined organizational pricing strategies in the presence of consumer resale. Phumchusri and Swann (2014) [47] concluded that the benefits from having flexibility of price changes and demand learning can complement each other to achieve as much as 8.15% revenue increase on average, as compared to static pricing. Kemper and Breur (2016) [48] through Monte-Carlo simulations showed that a dynamic ticket pricing policy for sports tickets is significantly more efficient than an optimal fixed price policy.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al (2012) [46] examined organizational pricing strategies in the presence of consumer resale. Phumchusri and Swann (2014) [47] concluded that the benefits from having flexibility of price changes and demand learning can complement each other to achieve as much as 8.15% revenue increase on average, as compared to static pricing. Kemper and Breur (2016) [48] through Monte-Carlo simulations showed that a dynamic ticket pricing policy for sports tickets is significantly more efficient than an optimal fixed price policy.…”
Section: Introductionmentioning
confidence: 99%